(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2016)
Wear is the main reason for the loss of performance of the parts for agricultural machinery. It leads to the degradation of the soil working quality. This work aims to highlight the wear resistance of the harrows discs manufactured, consolidated and sharpened differently. The tests were conducted in the laboratory and the field of the Faculty of Exploitation and Repair of Agricultural Machinery of the State Technical University of Kirovograd (Ukraine) in 2015. The technical equipment consists of devices for consolidation by electric discharge and for measurement the linear wear of discs, a harrow, a sand test bed, a tractor and discs made of different materials and technologies. Some parameterized were collected during the laboratory test each 5 ha and up to 20 ha of operation and in the fields each 30 ha until the time limit of exploitation. The Laboratory tests have shown that after twenty (20) ha of operation, the wear resistance of the experimental discs made of steel 65G and consolidated by electric discharge with simultaneous grinding (sharpening angle of 30°) is 2.95 times higher than the discs in series made of steel 28MnB5. The field experiment gave the following results: According to agro technical requirements, the plowing depth limit of serial discs made of steel 28MnB5 was reached after an operating duration of 120 ha while for experimental discs made of steel 65G and consolidated by electric discharge with simultaneous grinding (sharpening angle of 30 degrees) this duration is of 156 ha. The diameter wear limit of experimental discs was reached after an operating duration of 179 ha against 154 ha for the serial ones. Therefore, the new technology can be applied during the manufacture and / or the repair of the discs. Int. J. Agril. Res. Innov. & Tech. 5 (2): 70-74, December, 2015